Double activation of oxygen intermediates of oxygen reduction reaction by dual inorganic/organic hybrid electrocatalysts. (August 2021) - Lee, Dong-Gyu; Kim, Su Hwan; Lee, Jiyun; Shin, Seokmin; Joo, Se Hun; Lee, Yeongdae; Park, Chanhyun; Kwon, Youngkook; Kwak, Sang Kyu; Song, Hyun-Kon
Abstract: Synergistic effects of dual homogeneous catalysts for chemical reactions have been reported. Double activation (chemical transformation process where both catalysts work in concert to activate reactants or intermediates) was often responsible for the synergistic effects of dual catalyst systems. Herein, we demonstrate the extension of the double activation from chemo-catalysis to electrocatalysis. The activity of low-cost cobalt oxide electrocatalysts for oxygen reduction reaction (ORR) was significantly improved by introducing secondary-amine-conjugated polymers (HN-CPs) as the secondary promoting electrocatalyst (shortly, promoter). It was proposed that HN-CPs activated neutral diatomic oxygen to partially charged species (O2 δ- ) in the initial oxygen adsorption step of ORR. Electron donation number of HN-CP to diatomic oxygen (δ in O2 δ- ) well described the order of activity improvement, i.e., polypyrrole (pPy) > polyaniline (pAni) > polyindole (pInd). The maximum overpotential gain at ~150 mV was achieved by using pPy with the highest δ. Also, it was confirmed that proton of HN-CP was transferred to single oxygen intermediate (*O) of ORR. Graphical Abstract: ga1 Electrocatalytic activity of oxygen reduction reaction (ORR) on Co-based electrocatalyst as the primary inorganic catalyst is significantly improved by adding a secondary-amine conjugated polymer (NH-CP; e.g., polypyrrole) as the secondary organic catalyst. The NH-CP donates its electron to oxygen molecule to form O2 δ - and its proton to the single oxygen intermediate (*O). This dual inorganic/organic hybrid electrocatalyst system is the clear example of the double activation for heterogeneous electrocatalytic process. Highlights: The first example of heterogeneous electrocatalysis based on double activation is presented. Introduction of a secondary organic catalyst to a primary inorganic catalyst improved ORR activity. The secondary organic catalyst donated its electron to oxygen molecule to form O2 δ - . Also, the secondary organic catalyst donated its proton to the single oxygen intermediate (*O).